Paramètres socio-spatiaux, réseaux sociaux et budget d'activité chez un groupe de mâles chimpanzés : stabilité dans le temps et effet de la réduction spatiale - Nerea Amezcua‑Valmala; Daniel Vázquez; Álvaro Ballesteros; Marcos Bella; Catarina Casanova; Fernando Colmenares (Revue de Primatologie)
Within chimpanzee communities, males are well known for forming strong social bonds with one another. These bonds are most evident in the non-random patterns of associations, affiliations and proximity exhibited by males. In captivity, crowding conditions, demographic changes and other factors such as individuals’ maturity can modify social relationships, the type of interactions and also the way individuals manage conflicts. We believe that the combined study of grouping patterns, social networks, and activity budgets can provide a deeper understanding of the processes that drive behavioral changes under different conditions. With this in mind, we studied a group of male chimpanzees housed at La Vallée des Singes in France under two housing conditions, indoors (spatial crowding condition) and outdoors; and at two different time-points, in 2007 and 2009. In this period, the two most significant demographic changes were that most individuals reached maturity and that a chimpanzee died. We studied their grouping patterns (i.e. sociality, closeness and gregariousness), their social network and their activity budgets to examine how different changes of diverse nature affected their social structure and their interactions. Compared to outdoors, in the indoor condition, individuals stayed closer and were more sociable and gregarious. They also affiliated and aggressed more often indoor than outdoors. Their social network also varied, being the diameter smaller and the density higher indoors than outdoors. After analyzing the stability across time no differences were found in sociality, closeness and gregariousness but we observed an increase in self-directed behaviors from 2007 to 2009. Their social network varied, decreasing its diameter and increasing its density from 2007 to 2009. Our data would be in agreement with a coping model for conflict management since the chimpanzees altered their behavior by increasing affiliative behaviors and reducing proximity distances under spatial crowding conditions. Across time, changes in maturity and the death of a member did not affect proximity patterns in this colony. The mentioned increase of self-directed behaviors is usually interpreted as an index of stress; however, our data, as agonism and other measures remained stable from 2007 to 2009, should be interpreted with caution. Together with grouping patterns and activity budgets, the analysis of social networks allowed a better understanding of the variation in the social structure of this group. Partly funded by project grant SFRH/BD/69069/2010 to NAV and PSI2011-29016-C02-01 to FC.